Successful resolution of a tuberculous bronchopleural fistula presenting as recurrent pneumothorax in an atypical host: A case report - Aristia, Lintang Briliana; Subianto, Aries (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Secondary spontaneous pneumothorax (SSP) occurs in approximately 1-1.5% active tuberculosis (TB) cases, frequently progressing to a bronchopleural fistula (BPF) with a 2.89-fold increased risk. TB remains the primary etiology of SSP in high-burden regions like Indonesia, causing 46.15% of cases. Purpose: To describe the clinical presentation, diagnostic challenges, and successful multimodal management of a tuberculous bronchopleural fistula presenting as recurrent pneumothorax in an atypical host. Method: This descriptive analytic research used a case study approach involving a 43-year-old man patient with left-sided Secondary Spontaneous Pneumothorax attributed to underlying pulmonary tuberculosis at the Achmad Yani Surabaya Islamic Hospital. Data were collected through interviews, observation, physical examinations, medical records, and diagnostic documentation, using a head-to-toe assessment format. Data analysis was conducted concurrently with data collection, comparing findings with existing theories to support discussion and intervention recommendations. The analysis was narrative and observational, aiming to interpret the patient’s condition in relation to theoretical knowledge. Results: This case uniquely highlights tuberculous SSP in an immunocompetent host, underscoring the critical need for a high index of suspicion for TB, even without classic constitutional symptoms. Conservative therapy became innefective due to a persistent air leak which strongly indicated a BPF, a recognized complication in 69.2% of similar cases. This finding justified escalation to surgical management, aligning with international guidelines. The integrated multimodal management strategy proved crucial for a successful outcome. Conclusion: Active TB must be considered a primary differential diagnosis for SSP in endemic settings, regardless of typical clinical presentation. A persistent BPF demands definitive surgical intervention. The combination approach of ATT followed by VATS wedge resection and pleurodesis represents a highly effective and conclusive management strategy for these challenging cases.